Sociodemographic predictors of flourishing among community older adults in China - Yi, Xin; Liu, Xiaoyun; Liu, Xiaoqun; Chen, Gang; Xie, Yujie; Lin, Chenhao; Lv, Hangqin; Li, Yingchun; Wu, Shuang (Frontiers in Psychology, 2025)
Objective: With China becoming a rapidly aging society, the mental health of older adults has become an urgent concern. Past research on mental health assessment has primarily focused on psychopathological aspects such as depression or anxiety. In recent years, however, scholars in positive psychology have suggested that this may ignore the impact of individuals' positive psychological qualities, such as well-being. "Flourishing" is a novel concept in the field of wellbeing. This adds to psychological well-being based on traditional social and subjective well-being. However, limited research has focused on the flourishing of older Chinese community-dwelling adults from the perspective of positive psychology. Therefore, this study explored the status and factors influencing flourishing among older Chinese community-dwelling adults. Methods: A total of 518 community-dwelling older adults living in Chengdu between January 2022 and March 2022 were included in this study through a cross-sectional survey. Participants completed the General Condition Questionnaire and the Flourishing Scale. The data were collected and recorded in a database using a two-person input format. Data analysis was conducted using SPSS Windows software version 26.0. Multivariate linear regression analysis was used to identify the factors influencing flourishing. Results: The mean score of the flourishing scale among Chinese community-dwelling older adults was 40.8 ± 8.8. Univariate analysis showed that economic condition, education level, spousal state, social participation, daily exercise, and chronic disease were significantly associated with flourishing among community-dwelling older adults. In contrast, gender, place of residence, and living state were not. Multivariate linear regression analysis showed that economic condition (β=0.338, p＜0.001), education level (β=0.300, p＜0.001), spousal state (β=-0.291, p=0.008), social participation (β=-0.286, p=0.013), daily exercise (β=-0.407, p＜0.001), and chronic disease (β=0.313, p=0.002) were significant influence factors of flourishing among community-dwelling older adults. Conclusions: This study is one of the first to explore the growth of community-dwelling older adults in China. The findings of this study make essential contributions to existing research on well-being. Interventions targeting older adults with poor economic conditions, lower educational levels, chronic diseases, limited social participation, and widowed or living alone are necessary.